An "ethnically unique" athlete: An analysis of media representations of Jeremy Lin during the 2010–2011 and 2016–2017 NBA seasons. (September 2022) - He, Mu
Jeremy Lin, an Asian American basketball player, achieved his meteoric stardom by giving outstanding performances and leading the Knicks to constant wins. Intense media coverage and scholarly work about Lin had been done during this starring time, while this research focuses on media representations of Lin during regular seasons. This article employs textual analysis and examines 461 articles from the first and last NBA seasons Lin played. The thematic analysis shows media representations of Lin became more diverse while rarely using racialized narratives. However, untrust and low expectations of Asian American masculinity are discovered in the analysis. In addition, stereotypical narratives such as "see someone Asian, say something Asian, " and the model minority myth beautify stereotypical impressions of Asian Americans and exacerbate their "otherness." Such flattering compliments embedded in media coverage obfuscate Asian American identity, making it more difficult for them to prove their personality and masculinity. Although the media create and maintain hegemonic masculinity and stereotypes, they are also powerful to break down prejudice and discrimination and reshape people's impressions of Asian American athletes, and even their whole community.